Yield and nutritional value of silage of different sorghum hybrids inoculated with Azospirillum brasilense - Jucinéia Fernandes Souza; João Paulo Sampaio Rigueira; Carlos Juliano Brant Albuquerque; Vicente Ribeiro Rocha Júnior; Alexandre Soares dos Santos; Cinara da Cunha Siqueira Carvalho; Dijair Barbosa Leal; Bernado Marques Mendes; Rafael Augusto da Costa Parrella; Ranney Késsia Oliveira de Jesus Silva; Flávio Pinto Monção (Journal of Applied Animal Research, 2023)
The objective of this study was to evaluate sorghum hybrids associated or not associated with Azospirillum brasilense and nitrogen fertilization (N) during planting on the yield, fermentative profile, and nutritional value of the respective silages. Five sorghum hybrids (Volumax, 201813B, 201814B, 201709B, BRS716) were evaluated with three nitrogen fertilization strategies using urea (100 kg ha−1 of N) and Azospirillum brasilense, and urea (100 kg ha−1 of N)/A. brasilense in association. A randomized block design was used in a 5 × 3 factorial scheme, with five hybrids, three fertilization strategies and three replications (blocks). The useful area of each experimental unit was 3 m x 3 m. The biomass sorghum hybrids showed a dry matter (DM) production (P = 0.01) 48.31% higher than the DM production of the Volumax forage (mean of 17.49 t ha−1 of dry matter). There was no difference between the sorghum hybrid silages in the pH values (mean of 4.11; P = 0.68), gas losses (mean of 3.74% of DM; P = 0.19). The sorghum hybrids biomass 201709B and BRS 716 showed better digestible and DM productivity. Azospirillum brasilense can be used as a nitrogen fertilization strategy in partial or total replacement of urea.